A study on outcome of hepatic fibrosis in chronic hepatitis B patients on anti-viral therapy - Avick Nag,; Saubhik Ghosh,; Souvik Sarkar,; Soumya Sarathi Mondal,; Enamul Hossain,; Sanjay Kumar Mandal, (Asian Journal of Medical Sciences, 2024)
Background: Hepatitis B infection is a global public health problem. Chronic hepatitis B (CHB) infection leads to complications such as cirrhosis, liver failure, and hepatocellular carcinoma. Effective antiviral therapy significantly improves the stages of fibrosis in these patients. Hence, the liver stiffness measurement using transient elastography (Fibroscan) in CHB patients undergoing treatment is important to evaluate the effectiveness of the therapy and to predict the prognosis. Aims and Objectives: To see the outcome of Hepatic Fibrosis by non-invasive measurement in CHB patients after 6 months of oral anti-viral therapy. Materials and Methods: Seventy new CHB patients are included in a prospective hospital-based study and at the end of 6 months 53 patients were analysed. Results: Our study showed a significant statistical reduction in Liver Fibrosis as well as improvement of serological and biochemical parameters in CHB patients. Conclusion: There is liver fibrosis reversal in CHB patients after 6 months of anti-viral therapy and Fibroscan helps not only as a marker for initiation of treatment depending on the degree of fibrosis but also indicates the response or progression of the disease.